IDIOMS AND THEIR FUNCTIONS IN CONTEXTS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article notes that explanation of idioms, how to and their characteristics in context with particular examples. That is, an idiom is a statement that signifies something other than what its words appear to imply. Thus, an idiom is a frequent term or phrase that implies something other than its literal meaning, yet may be comprehended due to its widespread use and context. The article looked through the works of authors based on their analyses. This helps to linguistics and translators while explaining the meaning of idioms in the context to readers. Idioms are context dependent and context has a substantial impact on idiom comprehension.